PARTISIPASI MASYARAKAT MENGIKUTI PENDIDIKAN DI PTKIN (Studi terhadap Motivasi Spiritual Keagamaan) - Kisbiyanto, Kisbiyanto (Program Studi Pendidikan Agama Islam, 2016)
PUBLIC PARTICIPATION ON EDUCATION IN STATE COLLEGE ON ISLAMIC STUDIES (STUDY OF THE RELIGIOUS SPIRITUAL MOTIVATION). The purpose of this research was to know what factors which motivate individuals to participate the education in Islamic religious College. Informants in this study were the students’ parents as well as part of the community. The background of this research is that the Muslim community has certain considerations and viewpoints to participate in higher education. This study used mix methods by using quantitative-qualitative approach. The data were obtained using the technique of snow ball sampling by distributing questionnaire forms and direct survey on the students’ parents. The factors that motivate public participation to study in College, especially in the Tarbiyah Department, shows that college that specifically teaches Islamic studies becomes a major consideration as well as magnet for individuals to study in the college level. The consideration to do the religious orders and becoming a scholar of Islamic education is the highest motivation than any other motivations. Factor of carrying out the obligations to learn Islamic studies and extended learning also becomes the most important factor. All of those factores are the spiritual religious motivation portraits.